Secure Quantum Dialogue based on Non-orthogonal Entangled States and Local Unitary Operation - SANJU CHAUHAN; Dr. Narayan Lal Gupta (INFOCOMP Journal of Computer Science, 2024)
We introduce a secure quantum dialogue scheme characterized by non-orthogonal entangled states that use the concept of superdense coding to obtain optimum efficiency and high resource capacity. In this scheme, two non-orthogonal four-qubit cluster states are deployed as a quantum channel to communicate four-qubit secret information by encrypting only two qubits. By virtue of the non-orthogonality of the quantum channel, the current approach can effectively prevent various sorts of viable unauthorized access while establishing a robust quantum channel. Furthermore, two security checks and authentication processes make it more secure, and it also overcomes the disadvantage of information loss and is technically attainable with present technology.